Komodo dragons highlight Indonesian adventure - Rolston, Holmes, 1932-2025, author; Fort Collins Coloradoan, publisher (Colorado State University. Libraries, 2011)
Rolston account of a September 2011 trip to see Komodo dragons in the wild, on Komodo and Rinca Islands, Indonesia. Also Orange-footed Scrubfowl, or Megapodes.
Keywords: water-buffalo; wild boar; Komodo dragons; Komodo Island; Rinca Island; Flores Island; orange-footed scrubfowl; megapodes; parthenogenesis